# How do you solve -4x + 7= - 1( 2x - 3.5)?

Jun 11, 2018

x=1.75

#### Explanation:

ok first ya wanna multiply $- 1 \left(2 x - 3.5\right)$ which gets ya $- 2 x + 3.5$ (ya flipped the negatives to positives and vis versa) so at this point ya got $- 4 x + 7 = - 2 x + 3.5$ then ya wanna subtract 7 on both sides getting you $- 4 x = - 2 x - 3.5$ then add 2x on both sides so ya get $- 2 x = - 3.5$ so then ya wanna get x by it self so you divide -2 on both sides canceling the -2 on the left leaving you with $x = \frac{- 3.5}{- 2}$ which ya simplify down to 1.75

if ya need more clarification go to https://www.symbolab.com/solver/step-by-step/-4x%2B7%3D-1%5Cleft(2x-3.5%5Cright) which tells ya it step by step

Jun 11, 2018

$x = 1.75$

#### Explanation:

$- 4 x + 7 = - 1 \left(2 x - 3.5\right)$

Expand the right side by multiplying

$- 4 x + 7 = - 2 x + 3.5$

Move $x$ to the right side (add $4 x$ to both sides)

$7 - 4 x + 4 x = - 2 x + 3.5 + 4 x$

$7 = 2 x + 3.5$

Subtract $3.5$ from both sides

$7 - 3.5 = 2 x + 3.5 - 3.5$

$3.5 = 2 x$

Divide both sides by $2$

$\frac{2 x}{2} = \frac{3.5}{2}$

$x = 1.75$

Jun 11, 2018

See a solution process below:

#### Explanation:

First, expand the terms in parenthesis on the right side of the equation by multiplying each term within the parenthesis by the term outside the parenthesis.

$- 4 x + 7 = \textcolor{red}{- 1} \left(2 x - 3.5\right)$

$- 4 x + 7 = \left(\textcolor{red}{- 1} \times 2 x\right) + \left(\textcolor{red}{- 1} \times - 3.5\right)$

$- 4 x + 7 = - 2 x + 3.5$

Next, add $\textcolor{red}{4 x}$ and subtract $\textcolor{b l u e}{3.5}$ from each side of the equation to isolate the $x$ term while keeping the equation balanced:

$- 4 x + \textcolor{red}{4 x} + 7 - \textcolor{b l u e}{3.5} = - 2 x + \textcolor{red}{4 x} + 3.5 - \textcolor{b l u e}{3.5}$

$0 + 3.5 = \left(- 2 + \textcolor{red}{4}\right) x + 0$

$3.5 = 2 x$

Now, divide each side of the equation by $\textcolor{red}{2}$ to solve for $x$ while keeping the equation balanced:

$\frac{3.5}{\textcolor{red}{2}} = \frac{2 x}{\textcolor{red}{2}}$

$1.75 = \frac{\textcolor{red}{\cancel{\textcolor{b l a c k}{2}}} x}{\cancel{\textcolor{red}{2}}}$

$1.75 = x$

$x = 1.75$